Dynamiques climatiques en milieu sahélien sénégalais : perceptions locales et facteurs socioéconomiques associés dans le nord du Sénégal - Issa Mballo (VertigO, 2025)
Climate change is a threat in rural areas of sub-Saharan Africa that depend mainly on the primary sector. People try to adapt, but the modalities of adaptation depend on the differentiated way in which individuals perceive change. A theme that has so far been little studied. The present study therefore analyzes the perceptions of climate change among rural populations in northern Senegal and identifies the socioeconomic factors associated with them. Beforehand, it compares meteorological measurements and perceptions of the climate in the study area. It is based on a questionnaire administered to 905 households and on meteorological data from 1990 to 2021 from the Saint-Louis station. This study uses several methods, including the calculation of standardized precipitation and temperature indices and binary logistic regression, to determine the links between socioeconomic factors and the perception of climate change. Comparative analysis of the data showed overall some divergence between climate measurements and perceptions. The results of binary logistic regressions indicate that variables such as the respondent's literacy level, gender, ethnicity, and the level of food insecurity in some households affect the climate perception of individuals and households.